Chronic and Temporary Poverty in Australia: Targeting Public Transfers - Rodgers, J (My University, 2010)
This study investigates the efficacy of Australian public transfers in alleviating poverty, particularly chronic poverty. The larger the proportion of transfers received by people who would be poor in their absence, the better targeted the transfers. From 2001 to 2007, 64 per cent of all public transfers were received by people who would have been in chronic poverty according to their pre-transfer incomes. Another 22 per cent went to people in pre-transfer temporary poverty, whereas 14 per cent were received by people who were not poor based on their pre-transfer incomes. Family payments were less well-targeted than other public transfers.
The Economic Record
Keywords: Finance; Finance -- Poverty and Disadvantage; Income, wealth and finances; Finance; Poverty and Disadvantage; Income, wealth and finance